Respuesta :

remember that [tex]\int\limits_C {\vec{F} \cdot \vec{dr}} =\int\limits^a_b {\vec{F}(\vec{r}(t)) \cdot \frac{\vec{dr}}{dt}} \, dt[/tex]


[tex]\vec{F}(x,y,z)=<sin(x),cos(y), xz>[/tex]

[tex]\vec{r}(t)=<t^4,-t^3,t>[/tex], or [tex]x=t^4[/tex], [tex]y=-t^3[/tex] and [tex]z=t[/tex]

parametizing [tex]\vec{F}[/tex]

[tex]sin(x)=sin(t^4)[/tex]

[tex]cos(y)=cos(-t^3)[/tex]

[tex]xz=(t^4)(t)=t^5[/tex]

so [tex]\vec{F}(\vec{r}(t))=<sin(t^4),cos(-t^3),t^5>[/tex]


[tex]\frac{\vec{dr}}{dt}=\frac{d}{dt} \vec{r}(t)=<4t^3,-3t^2,1>[/tex]

calculate [tex]\vec{F}(\vec{r}(t)) \cdot \frac{\vec{dr}}{dt}}[/tex]

[/tex]<sin(t^4),cos(-t^3),t^5> \cdot <4t^3,-3t^2,1>=[/tex]

[tex](4t^3sin(t^4))+(-3t^2cos(-t^3))+(1t^5)=[/tex]

[tex]4t^3sin(t^4)-3t^2cos(-t^3)+t^5[/tex]

so evaluate integral


[tex]\int\limits_C {\vec{F} \cdot \vec{dr}} =\int\limits^a_b {\vec{F}(\vec{r}(t)) \cdot \frac{\vec{dr}}{dt}} \, dt=[/tex]

[tex]\int\limits^1_0 {4t^3sin(t^4)-3t^2cos(-t^3)+t^5} \, dt=[/tex] (using u subsitution with u=t^4 and for cosine, u=-t^3)

[tex][-cos(t^4)+sin(-t^3)+\frac{1}{6}t^6]|^1_0=[/tex]

[tex](-cos(1^4)+sin(-(1)^3)+\frac{1}{6}(1)^6)-(-cos(0^4)+sin(-(0)^3)+\frac{1}{6}(0)^6)=[/tex]

[tex](-cos(1)+sin(-1)+\frac{1}{6})-(-cos(0)+sin(0)+0)=[/tex]

[tex]-cos(1)+sin(-1)+\frac{1}{6}+1+0+0=[/tex]

[tex]-cos(1)+sin(-1)+\frac{7}{6}[/tex]

not sure if 1 is degrees or radians

ACCESS MORE